Irregular Proton Injection to High Energies at Interplanetary Shocks - Trotta Domenico; Horbury Timothy S.; Lario David; Vainio Rami; Dresing Nina; Dimmock Andrew; Giacalone Joe; Hietala Heli; Wimmer-Schweingruber Robert F.; Berger Lars; Yang Liu (Institute of Physics Publishing, 2025)
How thermal particles are accelerated to suprathermal energies is an unsolved issue, crucial for many astrophysical systems. We report novel observations of irregular, dispersive enhancements of the suprathermal particle population upstream of a high-Mach-number interplanetary shock. We interpret the observed behavior as irregular “injections” of suprathermal particles resulting from shock front irregularities. Our findings, directly compared to self-consistent simulation results, provide important insights for the study of remote astrophysical systems where shock structuring is often neglected.